Effect of graphene on friction and wear behavior of friction composite tested against grey cast iron disc alloyed with copper. (April 2021) - Ravikumar, N.; Tamilarasan, T.R.; Rajendran, R.
Abstract: The tribological properties of tribo-pair of friction composite and counter disc are very important for identifying the braking performance in automobiles. Among the various factors influencing the friction and wear of the tribo-pair, the ingredients of the friction composite and material of the disc are significant. In the present study, a new tribo-pair was formed between the friction composite with graphene nanopowder (GNP) and grey cast iron disc alloyed with copper (CuGCI). The tribo pair thus formed was tested in a pin-on-disc machine under dry sliding condition and its performances were compared with the other tribo-pairs formed between friction composites with graphite (Gr), Molybdenum di sulphide (MoS2 ) and disc. Five composites - 20 wt% MoS2, 20 wt % Gr, 20 wt % GNP, 15 wt % GNP, 10 wt % GNP - were tested against GCI and CuGCI disc thus forming ten different tribo-pair. Results showed that the tribo pair of 10 wt % GNP - CuGCI and 15 wt % GNP - CuGCI proved to have good friction and wear performances compared to the other tribo pairs and also at par with the performance of the commercial pad tested under the same conditions. Graphical Abstract: Image, graphical abstract